Gastroenterology issues in the public system of health care - Piasecki, Ryszard; Celiński, Krzysztof; Dworzański, Tomasz; Słomka, Maria (Polish Journal of Public Health, 2010)
The system of public medical care in Poland lacks uniform standards identifying basic principles of cooperation between general practitioners, consultants and hospital physicians within the range of gastroenterology. Presently, the area of gastroenterology in regard to daily health care is widely discussed.This study focuses on major aims, tasks and advantages of the implementation of comprehensive health care within gastroenterology as well as it reflects most relevant aspects of limitations regarding possible development of the above issues. This work presents recommended strategy for dealing with patients affected with the following diseases: gastric reflux disease, dyspepsia, chronic ulcer disease, gastrointestinal hemorrhage, inflammatory bowel diseases, irritable bowel syndromes, chronic diseases of liver and chronic pancreatitis.